2022
DOI: 10.1093/neuonc/noac079.067
|View full text |Cite
|
Sign up to set email alerts
|

DIPG-10. A Phase I trial of panobinostat following radiation therapy in children with diffuse intrinsic pontine glioma (DIPG) or H3K27M-mutated thalamic diffuse midline glioma (DMG): Report from the Pediatric Brain Tumor Consortium (PBTC-047)

Abstract: INTRODUCTION: Panobinostat is an oral HDAC inhibitor with pre-clinical activity against DIPG. The phase I study in children with progressive DIPG (stratum 1) defined the maximum-tolerated dose (MTD) as 10 mg/m2 administered 3x/week, 3 weeks on/1 week off. Herein, we report results of stratum 2, involving children with non-progressive DIPG/DMG using an alternative schedule. Primary objectives were to describe the toxicity profile and define the MTD; secondary objectives were to describe progression-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…By applying the estimated pharmacokinetic parameters from clinical plasma data and K p,uu obtained in our mouse model to predict the brain concentration-time profile in patients, we were able to demonstrate that, following multiple 20 mg oral doses, there was inadequate exposure of active panobinostat in the brain to treat brain tumors like medulloblastoma and DMG. The low exposure of free panobinostat in the brain shown in our simulation can help explain the lack of in vitro-in vivo correlation for oral panobinostat in clinical studies for CNS tumors (Lee et al, 2015;Wood et al, 2018;Monje et al, 2022). This delivery issue can be supported by the undetectable level of panobinostat in patients' CSF following systemic dosing.…”
Section: Discussionmentioning
confidence: 75%
“…By applying the estimated pharmacokinetic parameters from clinical plasma data and K p,uu obtained in our mouse model to predict the brain concentration-time profile in patients, we were able to demonstrate that, following multiple 20 mg oral doses, there was inadequate exposure of active panobinostat in the brain to treat brain tumors like medulloblastoma and DMG. The low exposure of free panobinostat in the brain shown in our simulation can help explain the lack of in vitro-in vivo correlation for oral panobinostat in clinical studies for CNS tumors (Lee et al, 2015;Wood et al, 2018;Monje et al, 2022). This delivery issue can be supported by the undetectable level of panobinostat in patients' CSF following systemic dosing.…”
Section: Discussionmentioning
confidence: 75%
“…It was reported that panobinostat had limited tolerability and variable pharmacokinetics in the paediatric patients with DIPG/DMG and showed no clinical benefit between treatment groups. It was suggested that further treatment regimens, enhanced drug delivery methods and combination therapies should be considered in future clinical studies using panobinostat 129 . Other clinical studies that use panobinostat include a phase 1 trial using Marizomib, a proteasome inhibitor in combination with panobinostat in pHGGs (NCT04341311) and phase 1/2 trials that are looking at the safety profile and drug tolerability of MTX110, a water soluble nanoformulation of panobinostat, in children newly diagnosed with DIPG (NCT03566199 and NCT04264143).…”
Section: Targeting Epigenetic Alterations: Alternative Diagnostic And...mentioning
confidence: 99%
“…While vorinostat was well tolerated it did not have any effect on survival with 1-year EFS of 5.85% ( Su et al, 2022 ) This negative result was likely multifactorial, with some contribution being limited CNS penetration ( Hanson et al, 2013 ; Guntner et al, 2020 ). Panobinostat has been studied in a phase 1 trial through the Pediatric Brain Tumor Consortium (PBTC) for DIPG, with results having recently being published ( Cooney et al, 2018 ; Monje et al, 2022 ). In the first stratum of patients, the maximal tolerated dose on a schedule of 3 weeks on/1 week off M/W/F was lower than expected at 10 mg/m2/dose with dose-limiting toxicities (DLT) being primarily hematologic.…”
Section: Epigenetic Programming and Combination Strategiesmentioning
confidence: 99%